Mixed lead–tin perovskite films with >7 μs charge carrier lifetimes realized by maltol post-treatment. Issue 40 (27th September 2021) - Hu, Shuaifeng; Truong, Minh Anh; Otsuka, Kento; Handa, Taketo; Yamada, Takumi; Nishikubo, Ryosuke; Iwasaki, Yasuko; Saeki, Akinori; Murdey, Richard; Kanemitsu, Yoshihiko; Wakamiya, Atsushi
Abstract : Maltol, a metal binding agent, effectively passivates defects on the surface of mixed lead–tin perovskite films. The carrier lifetimes of the resultant perovskite films are over 7 μs. The solar cell devices exhibit efficiencies of up to 21.4%. Abstract : Mixed lead–tin (Pb–Sn) halide perovskites with optimum band gaps near 1.3 eV are promising candidates for next-generation solar cells. However, the performance of solar cells fabricated with Pb–Sn perovskites is restricted by the facile oxidation of Sn(ii ) to Sn(iv ), which induces self-doping. Maltol, a naturally occurring flavor enhancer and strong metal binding agent, was found to effectively suppress Sn(iv ) formation and passivate defects in mixed Pb–Sn perovskite films. When used in combination with Sn(iv ) scavenging, the maltol surface treatment led to high-quality perovskite films which showed enhanced photoluminescence intensities and charge carrier lifetimes in excess of 7 μs. The scavenging and surface treatments resulted in highly reproducible solar cell devices, with photoconversion efficiencies of up to 21.4% under AM1.5G illumination.